Highly active Pt catalysts promoted by molybdenum-doped SnO2 for methanol electrooxidation. (11th May 2015) - Lu, Guo-Ping; Ma, Xian-Bin; Yang, Hai-Fang; Kong, De-Sheng; Feng, Yuan-Yuan
Abstract Composite oxides (MoO3)mSnO2 (m being the atomic Mo/Sn ratio) are prepared and employed as the promoter to Pt toward methanol electrooxidation reaction (MOR) in alkaline electrolyte. The Pt electrocatalysts supported on (MoO3)mSnO2/C are comprehensively characterized by TEM, XRD, XPS and electrochemical techniques. Electrochemical measurements for MOR indicate that molybdenum-doped SnO2 show much higher promotion effect to the catalytic performances of Pt than the undoped SnO2. The activities of Pt in Pt–(MoO3)mSnO2/C catalysts are also much higher than those in commercial Pt/C catalyst. Among the series of Pt–(MoO3)mSnO2/C catalysts, Pt–(MoO3)0.2SnO2/C shows the highest catalytic performances. The mass-specific activity (MSA) and intrinsic activity (IA) of Pt in Pt–(MoO3)0.2SnO2/C is ca. 3.0 and 3.5 times higher than those of Pt/C catalyst, respectively. The high content of Pt(II and IV) in the catalysts and the changes in Pt electronic structure are responsible for this improvement. These data suggest that the composite metal oxides (MoO3)mSnO2 are effective promoter to Pt toward MOR, which would be promising in designing new catalysts for high-performance alkaline direct methanol fuel cells and other technologies.